Cognitive dysfunction: A growing link between diabetes and Alzheimer's disease. Issue 2 (5th August 2019) - Jash, Kavya; Gondaliya, Piyush; Kirave, Prathibha; Kulkarni, Bhagyashri; Sunkaria, Aditya; Kalia, Kiran
Abstract: Diabetes mellitus (DM) is a gradually rising metabolic disease which is currently affecting millions of people worldwide. Diabetes is associated with various complications like nephropathy, neuropathy, retinopathy, diabetic foot, cognitive impairment, and many more. Evidence suggests that cognitive dysfunction is a rising complication of diabetes which adversely affects the brain of patients suffering from diabetes. Age‐related memory impairment is a complication having its major effect on people suffering from diabetes and Alzheimer's. Patients suffering from diabetes are at two times higher risk of developing cognitive dysfunction as compared with normal individuals. Multiple factors which are involved in diabetes related complications are found to play a role in the development of neurodegeneration in Alzheimer's. The problem of insulin deficiency and insulin resistance is well reported in diabetes but there are many studies which suggest dysregulation of insulin levels as a reason behind the development of Alzheimer's. As the link between diabetes and Alzheimer disease (AD) is deepening, there is a need to understand the plausible tie‐ins between the two. Emerging role of major factors like insulin imbalance, advanced glycation end products and micro‐RNA's involved in diabetes and Alzheimer's have been discussed here. This review helps in understanding the plausible mechanism underlying the pathophysiology of amyloid beta (Aβ) plaque formation and tau hyperphosphorylation as well provides information about studies carried out in this area of research. The final thought is to enhance the scientific knowledge on this correlation and develop future therapeutics to treat the same. Abstract : Cognitive dysfunction is the major correlation between diabetes and Alzheimer's which is nowadays known as "Alzheimer's type 3 diabetes." Several factors like insulin, accumulation of AGE products and GSK‐3β involved in diabetes and factors like Aβ plaque, tau protein hyperphosphorylation and miRNAs involved in neurodegeneration are involved in reinforcing the camaraderie between the two. AGE, advanced glycation end products; Aβ, amyloid beta; GSK‐3β, glycogen synthase kinase 3 beta; miRNA, micro‐RNA.